2010
DOI: 10.1016/j.jvs.2010.01.058
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary 3D computational analysis of the relationship between aortic displacement force and direction of endograft movement

Abstract: Objective Endograft migration is usually described as a downward displacement of the endograft with respect to the renal arteries. However, change in endograft position is actually a complex process in three dimensional space. Currently, there are no established techniques to define such positional changes over time. The purpose of this study is to determine whether the direction of aortic endograft movement as observed in follow-up CT scans is related to the directional displacement force acting on the endogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 23 publications
3
48
0
1
Order By: Relevance
“…While the exact timing of when the coarctation is alleviated in vivo was not precisely determined, the product literature provides an initial strength of Ïł15 lbf and a known strength retention curve based on the number of days since suture implementation. An analysis using this retention curve with our previous CFD results and knowledge of rabbit aortic diameters indicates that the force exerted on the suture used to create the coarctation by integrating the distribution of tractions within this region (22) exceeds the strength indicated by the manufacturer after Ïł21 days. Importantly, this information suggests that the approach of inducing CoA with dissolvable Vicryl suture used for the present investigation provides the stimulus of altered hemodynamic from CoA for 3 wk before restoring BP to normal for ÏŸ4 mo (Ïł6 human years) before the experimental end point.…”
Section: Discussionmentioning
confidence: 83%
“…While the exact timing of when the coarctation is alleviated in vivo was not precisely determined, the product literature provides an initial strength of Ïł15 lbf and a known strength retention curve based on the number of days since suture implementation. An analysis using this retention curve with our previous CFD results and knowledge of rabbit aortic diameters indicates that the force exerted on the suture used to create the coarctation by integrating the distribution of tractions within this region (22) exceeds the strength indicated by the manufacturer after Ïł21 days. Importantly, this information suggests that the approach of inducing CoA with dissolvable Vicryl suture used for the present investigation provides the stimulus of altered hemodynamic from CoA for 3 wk before restoring BP to normal for ÏŸ4 mo (Ïł6 human years) before the experimental end point.…”
Section: Discussionmentioning
confidence: 83%
“…4,22,23 As an extension of these measurements, in recent studies, stent graft movement in all three spatial directions was explored, which might have an influence on stent graft migration. 9,11,24 Rafii et al 11 showed that, with a mean lateral stent graft movement of 9 mm, the rate of type 1 endoleaks was significantly higher than in patients without lateral movement. The authors assumed that these results represented a clinically relevant predictor of late adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Two different working groups reported that pulsatile forces of blood flow, referred to as migration forces, displacement forces, or drag forces, are responsible for the longitudinal movement of the stent graft. 9, 10 Rafii et al 11 focused on the lateral movement of the stent graft, and reported a significantly higher longitudinal migration in patients with a mean 9 mm of lateral deflection. Furthermore, this patient group presented with a significantly higher rate of type 1 endoleaks and the need for secondary interventions.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 These investigators found that pulsatile displacement force acting on an endograft is in a sideways direction with respect to the axis of the blood flow rather than in the downstream direction of blood flow. In these patient-specific models, 72% of the total displacement force on the endograft was directed sideways.…”
Section: Table III Secondary Interventions In the Nd And Sd Groupsmentioning
confidence: 99%